Preoperative carboplatin and paclitaxel-based chemoradiotherapy for esophageal carcinoma: results of a modified CROSS regimen utilizing radiation doses greater than 41.4 Gy. Issue 6 (1st September 2016) - Nabavizadeh, N.; Shukla, R.; Elliott, D. A.; Mitin, T.; Vaccaro, G. M.; Dolan, J. P.; Maggiore, R. J.; Schipper, P. H.; Hunter, J. G.; Thomas, C. R.; Holland, J. M.
Summary: Trimodality therapy for resectable esophageal and gastroesophageal junction cancers utilizing preoperative radiotherapy with concurrent carboplatin and paclitaxel-based chemotherapy is being increasingly utilized secondary to the results of the phase III CROSS trial. However, there is a paucity of reports of this regimen as a component of chemoradiotherapy in North America. We aim to report on our clinical experience using a modified CROSS regimen with higher radiotherapy doses. Patients with advanced (cT2–cT4 or node positive) esophageal or gastroesophageal junction carcinoma who received preoperative carboplatin/paclitaxel-based chemoradiotherapy with radiation doses of greater than 41.4 Gray (Gy) followed by esophagectomy were identified from an institutional database. Patient, imaging, treatment, and tumor response characteristics were analyzed. Twenty-four patients were analyzed. All but one tumor had adenocarcinoma histology. The median radiation dose was 50.4 Gy. Pathologic complete response was achieved in 29% of patients, with all receiving 50.4 Gy. Three early postoperative deaths were seen, due in part to acute respiratory distress syndrome and all three patients received 50–50.4 Gy. With a median follow-up of 9.4 months (23 days–2 years), median survival was 24 months. Trimodality therapy utilizing concurrent carboplatin/paclitaxel with North American radiotherapy doses appeared to have similar pathologic complete response rates compared with the CROSS trial, but may be associated with higher toxicity. Although the sample size is small and further follow-up is necessary, radiation doses greater than 41.4 Gy may not be warranted secondary to a potentially increased risk of severe radiation-induced acute lung injury.